Hydrogen-diesel dual-fuel direct-injection (H2DDI) combustion under compression-ignition engine conditions - Rorimpandey Patrick; Yip Ho Lung; Srna Aleš.; Zhai Guanxiong; Wehrfritz Armin; Kook Sanghoon; Hawkes Evatt R.; Chan Qing Nian (Elsevier Ltd, 2022)
This study investigates the ignition and combustion characteristics of interacting diesel-pilot and hydrogen (H2) jets under simulated compression-ignition engine conditions. Two converging single-hole injectors were used to inject H2 and diesel-pilot jets into an optically accessible constant-volume combustion chamber (CVCC). The parameters varied include fuel injection sequence, timing between injections, and ambient temperature (780–890 K). The results indicate that when diesel-pilot is injected before H2, with increasing time separation, the burnt diesel products mix and cool down, requiring longer jet-jet interaction to ignite the H2 jet. When H2 is injected before diesel-pilot, the H2-air mixing amount prior to pilot-fuel igniting impacts the combustion spreading through the H2 jet. If ignition of the H2 jet occurs beyond its end-of-injection (EOI), the H2 mixture zone where the pilot-diesel interacts with becomes too lean for combustion. At lower ambient temperatures, the combustion variability increases, attributed to the diesel-pilot lean out.